Pelatihan Menjadi Backend Developer Dengan Framework Laravel Pada Siswa Dan Siswi SMK Swasta Free Methodist Medan - M. Rhifky Wayahdi; Fahmi Ruziq; Subhan Hafiz Nanda Ginting (Jurnal Pengabdian Masyarakat Nusantara, 2024)
Every year, around 400,000 people in Indonesia graduate from information technology colleges and vocational schools. The human resources produced do not meet the standards required by the industry today. To become a software developer, you must have strong abilities. SMK Free Methodist Medan students will gain a basic understanding of website structure, tools used to create websites, technological advances, career paths as web developers, how to design the appearance of a website, and learn to use the Laravel framework to become a reliable backend developer. According to the author, the results of community service at the SMK Free Methodist Medan with training bases and methods are very beneficial for students because of their high enthusiasm for participating. This training will teach participants various skills and knowledge about website development as a backend developer. Participants provided feedback that this training really helped them in preparing for a career as a web programmer, especially a backend developer